O negrismo e suas configurações em romances brasileiros do século XX (1928-1984) - Luiz Henrique Silva de Oliveira (2013)
This work aims to conceptualize negrismo as a twentieth century literary procedure, and to study its manifestations in Brazilian novels. Therefore, in order to establish a dialogue with other meanings implied in the term, it is necessary to investigate its origins and its influences. Futhermore, it aims to characterize each of the negristas facets as main compositional-aesthetic procedure. The work is based on a corpus formed by Macunaíma (1928), by Mário de Andrade, A marcha (1941), by Afonso Schmidt, A casa da água (1969), by Antônio Olinto, Os tambores de São Luís (1975), by Josué Montello, Xica da Silva (1976), by João Felício dos Santos, and Viva o povo brasileiro (1984), by João Ubaldo Ribeiro. Finally, it is our purpose to demonstrate how the negristas Brazilian novel written in the period in question represents a stage of transition between the literature of ethnocentric perspective in relation to the black subject, and African- Brazilian Literature as such.